Development of Science Learning Media Based on Science Literacy on the Topic of Series and Parallel Circuits in Junior High School - Iju, Maria Vianney; Dinatha, Ngurah Mahendra; Rewo, Josep Marsianus; Kua, Maria Yuliana (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
Students at St. Agustinus Langa who lack scientific literacy are less able to react to local natural events and technological advancements. The purpose of this study is to describe the procedures used to create science learning resources based on scientific literacy using series and parallel series materials. This study employs the five stages of the ADDIE model—analysis, design, development, implementation, and evaluation—as a research and development (R&D) methodology. SMP St. Augustine Langa's class VIII students served as the research subjects. The study's findings demonstrate that using scientific literacy-based science learning materials in series and parallel series content can improve students' comprehension of the subject matter. The educational materials according to the research findings, St. Mary's Middle School students' understanding of scientific literacy has increased as a result of the creation of science learning materials based on scientific literacy in series and parallel circuit content. Langa, Augustine. Therefore, science learning media based on scientific literacy is appropriate for use in the science learning process. The implications of learning media created in the teaching and learning process include helping teachers explain learning material, improving the quality of the teaching and learning process in this case, and creating a pleasant learning atmosphere with the teaching and learning.